2021
DOI: 10.34260/jaebs.514
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Deviance in Public Sector Organizations: Evidence from Pakistan

Abstract: Deviant workplace behaviors have become an important area of research due to the recent revelation of high-profile corporate scandals. Scholars view that deviant workplace behaviors can be controlled when the factors that affect workplace deviance are properly understood. Therefore, this study is having two sections. Section one identifies the level of workplace deviance prevailing in the public sector hospitals of Pakistan, for which data was collected from 219 respondents in the understudy sector. Findings o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Similarly, Rudolph, Katz, Lavigne, and Zacher (2017) stated that crafting nurses' jobs will reduce their motivation to engage in inappropriate and uncivil behavior at work. On the contrary, the findings of Shah, Shah, Ullah, and Yasir (2021) concluded that workplace deviance exists in organizations in Pakistan; those behaviors appear as theft, willful disobedience of a supervisor's orders, pestering, slander, conspiracy, assigning blame to coworkers, and purposeful tardiness to work, all prohibited behaviors. Also, the results of Abubakar, Megeirhi, and Shneikat (2018) show that workplace incivility is prevailing in modern administrations, while experimental indications of incivility remain in their nascent phases in Arab localities.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, Rudolph, Katz, Lavigne, and Zacher (2017) stated that crafting nurses' jobs will reduce their motivation to engage in inappropriate and uncivil behavior at work. On the contrary, the findings of Shah, Shah, Ullah, and Yasir (2021) concluded that workplace deviance exists in organizations in Pakistan; those behaviors appear as theft, willful disobedience of a supervisor's orders, pestering, slander, conspiracy, assigning blame to coworkers, and purposeful tardiness to work, all prohibited behaviors. Also, the results of Abubakar, Megeirhi, and Shneikat (2018) show that workplace incivility is prevailing in modern administrations, while experimental indications of incivility remain in their nascent phases in Arab localities.…”
Section: Discussionmentioning
confidence: 98%
“…Third, the health-care sector is selected for this study, because it provides health-care services to the people of Pakistan and can help in maintaining a healthy human capital that may contribute to the flourishing and development of this country and its society (Irfan and Ijaz, 2011). But unfortunately, the public health-care sector of Pakistan is at the front with the challenges related to the deviant behaviors of its staff members (Ahmed et al , 2013; Shah et al , 2021). Moreover, nurses play an important role in the performance of a hospital.…”
Section: Methodsmentioning
confidence: 99%
“…Workplace deviance can be identified as compromising or threatening the very foundation of an organization on purpose (Shah et al , 2021; Yasir and Rasli, 2018). Workplace deviance is defined as “voluntary conduct that breaches major organizational standards and thereby jeopardizes the welfare of an organization, its members, or both” (Robinson and Bennett, 1995).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, now public sector organizations are also focusing on increasing work engagement in order to retain their valuable talent as the engaged and committed employees are more productive, creative and loyal with the organization, who in turn lead to the enhancement of overall performance of the organization (Memon et al, 2020;Sarmad et al, 2020). Shah, Shah, Ullah, and Yasir (2021) noted that public sector of Pakistan is also focusing on enhancing employees' engagement to increase their overall work performance. This changing is primarily occurring due to governmental preferences of changing government institutions into semi-government to increase their performance.…”
Section: Problem Statementmentioning
confidence: 99%